2018
DOI: 10.1016/j.aucc.2017.02.070
|View full text |Cite
|
Sign up to set email alerts
|

The challenges in caring for morbidly obese patients in Intensive Care: A focused ethnographic study

Abstract: Bariatric care pathways need to be developed that use more suitable body measurements to inform the use of bariatric equipment. Intensive care staff need to engage in debate about what is acceptable, respectful, and appropriate language in the delivery of bariatric patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
0
33
0
2
Order By: Relevance
“…Providing satisfactory care became difficult because of challenges in relation to the patients’ weight and the risk of complications. Hales, Coombs, and de Vries () also revealed that ICU staff found it physically challenging caring for morbidly obese patients. They revealed that special equipment was designed based on weight and not body shape, which resulted in difficulties in the care situations (Hales et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing satisfactory care became difficult because of challenges in relation to the patients’ weight and the risk of complications. Hales, Coombs, and de Vries () also revealed that ICU staff found it physically challenging caring for morbidly obese patients. They revealed that special equipment was designed based on weight and not body shape, which resulted in difficulties in the care situations (Hales et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Hales, Coombs, and de Vries () also revealed that ICU staff found it physically challenging caring for morbidly obese patients. They revealed that special equipment was designed based on weight and not body shape, which resulted in difficulties in the care situations (Hales et al., ). In the present study, physically demanding work caused nurses to worry for their own safety, and, as such, be “unwilling” to provide care.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, urgent procedures could be more difficult to achieve (resuscitation maneuvers, intubation, drip insertion), clinical signs could be shaded, treatments’ dosages must be adapted correctly and imaging strategies are different (less relevance or success of ultrasonography) [ 16 20 ]. There are also logistical difficulties because of inadequate material (limited access to bariatric chairs or beds) and obese patients need more staff for nursing procedures which are longer than for normal-weight patients [ 21 ]. Finally, the complexity of these situations seems to increase with the obesity’s severity.…”
Section: Introductionmentioning
confidence: 99%
“…In the anthropology of health and nutrition (e.g., Lee et al 2019;Thuita et al 2018), specific social, economic, and cultural factors affecting illnesses and nutrition in different cultural contexts have been identified to design more effective interventions (see G. H. Pelto [2017] for a review). In health care research (e.g., Bikker et al 2017;Hales et al 2018;Higginbottom et al 2013;Muecke 1994;Wall 2015), it has been shown that people from various cultures, subcultures, and groups integrate health beliefs and practices into their lives differently, and the social and cultural factors shaping health-care use and delivery have been identified (see Cruz and Higginbottom [2013] and Vindrola-Padros and Vindrola-Padros [2018] for reviews). Finally, in workplace studies, it has been shown that technological work systems are inseparable from the workers' local knowledge and reasoning, which produce the work actions and activities and make them understandable (see Luff et al [2000:xii-xvi] for a review).…”
Section: The Fem and Csr So Close Yet So Far The Femmentioning
confidence: 99%